Interaction of LRRK2 with kinase and GTPase signaling cascades - Boon, Joon Y.; Dusonchet, Julien; Trengrove, Chelsea; Wolozin, Benjamin (Frontiers in Molecular Neuroscience, 2014)
LRRK2 is a protein that interacts with a plethora of signaling molecules, but the complexity of LRRK2 function presents a challenge for understanding the role of LRRK2 in the pathophysiology of Parkinson’s disease. Studies of LRRK2 using over-expression in transgenic mice have been disappointing, however studies using invertebrate systems have yielded a much clearer picture, with clear effects of LRRK2 expression, knockdown or deletion in C. elegans and Drosophila on modulation of survival of dopaminergic neurons. Recent studies have begun to focus attention on particular signaling cascades that are a target of LRRK2 function. LRRK2 interacts with members of the MAPK pathway and might regulate the pathway action by acting as a scaffold that directs the location of MAPK pathway activity, without strongly affecting the amount of MAPK pathway activity. Binding to GTPases, GAPs and GEFs are another strong theme in LRRK2 biology, with LRRK2 binding to Rac1, cdc42, rab5, rab7L1, endoA, RGS2, ArfGAP1 and ArhGEF7. All of these molecules appear to feed into a function output for LRRK2 that modulates cytoskeletal outgrowth and vesicular dynamics, including autophagy. These functions likely impact modulation of α-synuclein aggregation and associated toxicity eliciting the disease processes that we term Parkinson’s disease.